Establishment of Inventory of Electronic Equipment Replacement Modules as a Way to Improve the Survivability of the Power System - Gurevich, Vladimir (International Journal of Electrical and Computer Engineering Systems, 2015)
The article discusses a way to improve the survivability of the power system affected by the High Altitude Electromagnetic Pulse (HEMP) through establishment of inventory of electronic equipment replacement modules, particularly those of digital protective relays. It is shown that the known methods of spare parts quantity optimization cannot be used in this case. Thus, another method is offered. Specific principles of the storage of replacement modules are discussed as well as the ways of their realization.